An unusual case of pneumocephalus after cardiac arrest in Qatar ICU facility - Phool Iqbal (12217770) (2022)
A 43 years old lady with good functional status, past medical history of myasthenia gravis since the age of 15 years, status post thymectomy complicated with laryngeal nerve injury and on tracheostomy tube, renal vein thrombosis due to the anti-phospholipid syndrome, and on anticoagulation with warfarin, came to the hospital with a history of drowsiness from 3 to 4 h at home which was not her baseline. There was no history of trauma, fall or alcohol use. Her GCS on arrival was 5/15. She underwent urgent CT brain and was found to have a subdural hematoma. Her baseline investigations revealed supratherapeutic INR of 10 and was given urgent fresh frozen plasma for correction. She did not have any other significant bleeding. She was kept under ICU for monitoring as per the neurosurgery plan. However, her hospital stay was complicated with sudden desaturation and three times respiratory arrests, each brief duration and lasting less than a minute. Further investigations, including urgent CT brain, later MRI brain, and evaluation of her tracheostomy tube via bronchoscopy, were remarkable for pneumocephalus as shown in Fig. 1, Fig. 2 and a granulation tissue obstructing the airways during respiration, respectively. ENT team was consulted and replaced the tracheostomy tube with a longer length to bypass the granulation tissue. Radiologist opinion regarding the unexpected CT brain finding was taken and suggested possible iatrogenic causes like a lumbar puncture or septic emboli. However, echocardiographic studies were unremarkable for any valvular disease or vegetation. Blood cultures were negative for any sepsis as well. Her pneumocephalus was managed conservatively with follow up of her GCS and serial CT scan as required. However, the patient did not improve and passed away in the next 72 h. Other Information Published in: Visual Journal of Emergency Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.visj.2022.101448